On the Shareholder Status of the Equity Assignee in Equity Transfer for Security - Kuang, Weiyan (International Journal of Social Sciences and Public Administration, 2025)
This article discusses the issue of whether the equity assignee in equity transfer for security enjoys the shareholder qualification within the corporate organization. There are disputes both in the theoretical circle and judicial practice regarding the shareholder status of the equity assignee in equity transfer for security within the corporate organization. The ambiguity in the legal framework of equity transfer pledges and the vagueness of standards for determining shareholder identity are the theoretical roots of the identification dilemma. Meanwhile, the encroachment of party autonomy on mandatory corporate law norms and the dualistic judicial approaches (differentiating between internal and external relationships) serve as practical catalysts for these challenges. To accurately ascertain the shareholder status of the equity transferee within the corporate framework in the context of equity transfer as security, it is imperative to meticulously elucidate the foundational legal architecture of equity transfer as security.Additionally, the legal provisions in the Company Law governing the determination of shareholder status should serve as the cornerstone for legal interpretation.